Metabolic and inflammatory linkage of the chicken cecal microbiome to growth performance - Wang, Liqi; Zhang, Fuping; Li, Hui; Yang, Shenglin; Chen, Xiang; Long, Shuihua; Yang, Shenghong; Yang, Yongxian; Wang, Zhong (Frontiers in Microbiology, 2023)
Introduction Chinese indigenous chicken breeds are widely used as food in China but their slow growth rate and long farming cycle has limited their industrial production. Methods In the current study we examined whether the market weights of native chicken breeds were related to specific cecal bacteria, serum metabolites and inflammatory cytokines. We examined cecal bacterial taxa using 16S rDNA analysis along with untargeted serum metabolites and serum inflammatory cytokines. Results We found that the cecal microbiota could explain 10.1% of the individual differences in chicken weights and identified key cecal bacterial genera that influenced this phenotype. The presence of Sphaerochaeta spp. improved growth performance via bovinic acid metabolism. In contrast, Synergistes and norank_f_Desulfovibrionaceae had a negative effect on growth by inducing expression of the inflammatory cytokine IL-6. Discussion We were able to link specific bacterial genera with growth promotion in chickens and this study will allow further development of their use as probiotics in these animals.